Redistribution of Return Inequality - Karl Schulz (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Wealthier households obtain higher returns on their investments than poorer ones. How should the tax system account for this return inequality? I study capital taxation in an economy in which return rates endogenously correlate with wealth. The leading example is a financial market, where the rich acquire more financial information than the poor. Contrary to conventional wisdom, rather than calling for more redistribution, the presence of this scale dependence provides a rationale for lower marginal tax rates. The endogeneity of returns generates an inequality multiplier effect between wealth and its returns. Therefore, standard elasticity measures that determine the responsiveness of capital to taxes must be revised upwards. At an aggregate level, a rise in redistribution induces a compression effect on the distribution of pre-tax returns. In the financial market, I identify general equilibrium trickle-up externalities that provide a force for more redistribution relative to the partial equilibrium. Finally, I estimate partial and general equilibrium responses and demonstrate the quantitative importance of scale dependence for tax policy.
Keywords: H21; H23; H24; D31; G11; G12; G14; G53; 330; optimal taxation; capital taxation; heterogeneous returns; wealth inequality; general equilibrium; asset pricing; private information; financial literacy